Synaptotagmin Ca2+ Sensors and Their Spatial Coupling to Presynaptic Cav Channels in Central Cortical Synapses - Bornschein, Grit; Schmidt, Hartmut (Frontiers in Molecular Neuroscience, 2019)
Ca2+ concentrations drop rapidly over a distance of a few tens of nanometers from an open voltage-gated Ca2+ channel (Cav), thereby, generating a spatially steep and temporally short-lived Ca2+ gradient that triggers exocytosis of a neurotransmitter filled synaptic vesicle. These non-steady state conditions make the Ca2+-binding kinetics of the Ca2+ sensors for release and their spatial coupling to the Cavs important parameters of synaptic efficacy. In the mammalian central nervous system, the main release sensors linking action potential mediated Ca2+ influx to synchronous release are Synaptotagmin (Syt) 1 and 2. We review here quantitative work focusing on the Ca2+ kinetics of Syt2-mediated release. At present similar quantitative detail is lacking for Syt1-mediated release. In addition to triggering release, Ca2+ remaining bound to Syt after the first of two successive high-frequency activations was found to be capable of facilitating release during the second activation. More recently, the Ca2+ sensor Syt7 was identified as additional facilitation sensor. We further review how several recent functional studies provided quantitative insights into the spatial topographical relationships between Syts and Cavs and identified mechanisms regulating the sensor-to-channel coupling distances at presynaptic active zones. Most synapses analyzed in matured cortical structures were found to operate at tight, nanodomain coupling. For fast signaling synapses a developmental switch from loose, microdomain to tight, nanodomain coupling was found. The protein Septin5 has been known for some time as a developmentally down-regulated ‘inhibitor’ of tight coupling, while Munc13-3 was found only recently to function as a developmentally up-regulated mediator of tight coupling. On the other hand, a highly plastic synapse was found to operate at loose coupling in the matured hippocampus. Together these findings suggest that the coupling topography and its regulation is a specificity of the type of synapse. However, to definitely draw such conclusion our knowledge of functional active zone topographies of different types of synapses in different areas of the mammalian brain is too incomplete.